Clay‐coat diversity in marginal marine sediments. Issue 3 (6th February 2019) - Wooldridge, Luke J.; Worden, Richard H.; Griffiths, Joshua; Utley, James E. P.
Abstract: The specific mineralogy of clay grain coats controls the ability of the coat to inhibit quartz cementation in sandstones during prolonged burial and heating. How and why clay‐coat mineralogy varies across marginal marine systems is poorly understood, even though these eogenetic phenomena strongly influence subsequent mesodiagenesis and reservoir quality. The novel development of the ability to predict the distribution of clay‐coat mineralogy would represent an important development for sandstone reservoir quality prediction. In marginal marine sediments, clay minerals occur as grain‐coats, floccules, mud intraclasts, clay‐rich rock fragments or as dispersed material. However, the relationships between clay mineralogy, the amount of clay, and its distribution is poorly understood. This study focused on the Ravenglass Estuary, UK. The key aim was to develop and apply a novel methodology utilising scanning electron microscope – energy dispersive spectrometry, for the first time, on grain coats in modern sediments, to differentiate the clay‐coat mineral signature from that of the bulk sediment, and reveal the distribution of clay minerals across marginal marine sediments. The study showed that marginal marine sediments principally have their clay mineral assemblage present as clay‐coats on sand grains. These clay‐coats have a mixed clay mineralogy and are spatially heterogeneous across the range of marginal‐marine depositional environments. The study further showed that clay‐coat mineralogy is governed initially by the hydrologically‐controlled segregation of the clay minerals within inner estuarine depositional environments, and subsequently by the selective abrasive removal of specific clay mineral types during reworking and transport into the outer estuary and the marine environment. The highest relative abundance of grain‐coating chlorite was in sand‐flat and tidal‐bar depositional environments. The availability of an analogue data set, and an understanding of the controlling processes of clay‐coat mineralogy, offer crucial steps in building a predictive capability for clay‐coat derived elevated reservoir quality in deeply buried sandstones.